SEXUAL HARASSMENT AND COPING STRATEGIES AMONG STUDENTS OF THE SCHOOL OF NURSING, UNIVERSITY COLLEGE HOSPITAL, IBADAN (2015)
Sexual Harassment (SH) which covers a continuum of behavioural patterns ranging from unwanted verbal advances to physical assault constitutes a major reproductive health concern worldwide. In Nigeria, studies have shown that students in institutions of higher learning are vulnerable to SH. However, its prevalence among student nurses has not been adequately explored. This study therefore determined the prevalence of SH among students of School of Nursing, University College Hospital (SNUCH), Ibadan. The descriptive cross-sectional study involved the use of a two-stage sampling technique in selecting 250 consenting nursing students at different levels of study at SNUCH. A pre-tested self-administered questionnaire containing information relating to students’ perception and prevalence of SH, its perpetrators, places of occurrence, types, consequences as well as coping strategies employed by victims was used for data collection. Descriptive and Chi-square statistics were used to analyze the data at 0.05 level of significance. Respondents’ mean age was 23.0 ± 4.1 years and 78.8% were females. Most respondents (91.2%) perceived SH to be common in the school. Fifty-eight percent of respondents comprising 11.6% males and 46.4% females had ever been sexually harassed. The main perpetrators of SH against female students included male resident doctors (24.5%), male patients (11.3%), male friends (7.5%), and male medical students (5.7%). Main harassers of males were female colleagues (44.8%) and female patients (20.7%). Common SH experienced included: unwanted body contact (79.3%) breast contact (67.6%), enticement (45.5%), attempted rape (39.3%) and unwanted kiss (26.3%). Perceived predisposing factors to SH included suggestive dressing (55.2%) and peer influence (56.0%). Places where SH occurred included hospital premises (28.2%), party (26.8%), reading rooms (20.0%) and classrooms (17.2%). The experienced adverse consequences included hatred (80.8%), depression (68.4%), fear of possible reoccurrence (74.8%) and loss of concentration on academics (68.0%). Significant association existed between respondents’ perception of prevalence of SH and experience of SH. Attending parties and wearing suggestive dresses were positively associated with incidence of SH. Though coping strategies adopted by the respondents was reported to be ineffective, the ones peculiar to males included reporting to school authority (72.0%), lecturers (62.1%) and confrontation (55.2%) while those peculiar to females iv included ignoring perpetrator (71.6%), avoidance (83.6%) and breaking relationship (85.3%). More males (82.7%) were dissatisfied with coping strategies employed than females (52.6%). More respondents in Basic Nursing programme (60.1%) were satisfied with coping strategies employed than their counterparts in Midwifery (45.0%), Perioperative (50.0%) and Occupational Nursing (40.0%). Fifty–seven percent of respondents were dissatisfied with handling SH personally while only 11.6% were satisfied with how reported cases were handled by the school authority. Sexual harassment is prevalent among the students of SNUCH, with females being more affected and coping strategies adopted were ineffective and unproductive. Institutional based interventions such as sensitization, coping strategy skills development, legislation and punitive policy reviews are needed to address these concerns.